Efficient hinterland transport infrastructure and services for large container ports - Michele Acciaro; Alan McKinnon (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
The growth in container volumes and the concentration of container flows on a limited number of hubs, which derives, among other things, from the increasing vessel size, requires the development of new terminal infrastructure at ports able to handle the latest generation of vessels. In addition to the pressure that such vessels impose on the terminal cargo handling capabilities, it is often forgotten, that those larger vessels will also require higher capacity in hinterland transportation or a rationalization and better use of existing transport alternatives. Those ports that are already plagued by inland congestion or that are located in the proximity of densely populated areas, will have to come up with viable alternatives to reduce the impact of congestion and relieve local communities from the negative externalities generated by increasing cargo flows. The development of new terminal infrastructure should then take into account the effects that increasing traffic volumes will have on the existing infrastructure and plan for expansion if necessary. As volumes increase, alternative modes of transport, such as rail or short-sea shipping are being promoted both to reduce both congestion and environmental impacts. In the specific case of Chile and the new development associated with the Puerto de Gran Escala project, it is imperative to carefully plan the development of the hinterland infrastructure. This is not only necessary to ensure that the investment yields adequate economic benefit; it must also maximise the social and environmental sustainability of the project. This paper provides an overview of the state of the art in hinterland transport management, focusing on the challenges that the development of new container terminal infrastructure is likely to bring to the local communities. Recommendation and a set of good practice case studies of good practice are also provided.
Keywords: 330; hinterland transportation; port gate; port hinterland; rail access to terminals; container terminals; emissions